Development of a novel optimization algorithm for a microstrip patch antenna array - Fredelino A. Galleto Jr; Aaron Don M. Africa; Ara Jyllian A. Abello; Joaquin Miguel B. Lalusin (Institute of Advanced Engineering and Science, 2024)
Microstrip patch antennas are typically used because they have a low profile and cost. The main theme of this study is to present a novel 2×2 microstrip antenna array design using rough set theory. In designing the 2×2 microstrip antenna array, an FR4 dielectric substrate was used to improve the performance. The rough set theory was used to optimize the microstrip antenna parameters. The FR4 dielectric substrate compared better to the microstrip patch antenna array wherein no substrate was used. The antenna with no substrate used had the energy that is radiating underneath which contributed to the sidelobes of the radiation pattern whereas the use of the substrate reduced the energy radiated at the substrate. Furthermore, the gains of the two were also simultaneously evaluated and it showed that the microstrip antenna array with the dielectric substrate had better gain than the one without. This 2×2 microstrip array antenna design may be used for applications such as mobile communications since it is small in size and performs well.